Cdc48 and a ubiquitin ligase drive disassembly of the CMG helicase at the end of DNA replication - Maric, Marija (Science, 2014)
Chromosome replication is initiated by a universal mechanism in eukaryotic cells, involving the assembly and activation at replication origins of the CMG (Cdc45-MCM-GINS) DNA helicase, which is essential for the progression of replication forks. Disassembly of CMG is likely to be a key regulated step at the end of chromosome replication, but the mechanism was unknown until now. Here we show that the ubiquitin ligase known as SCF(Dia2) promotes ubiquitylation of CMG during the final stages of chromosome replication in Saccharomyces cerevisiae. The Cdc48/p97 segregase then associates with ubiquitylated CMG, leading rapidly to helicase disassembly. These findings indicate that the end of chromosome replication in eukaryotes is controlled in a similarly complex fashion to the much-better-characterized initiation step.